2018
DOI: 10.1016/j.rmed.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Favorable association of polyphenol-rich diets with lung function: Cross-sectional findings from the Moli-sani study

Abstract: A higher overall polyphenol content of human diet was associated with better pulmonary function in a general population. The association might be partially mediated by WBC in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…In a recent randomized trial in COPD patients, supplementation with flavonoids in the form of oligomeric pro-anthocyanidins extracted from grape seeds was effective in improving oxidative stress and lipid profile, but not lung function parameters after 8 weeks [75]. More recent observational findings in a Mediterranean population confirmed protective effects of the intake of various polyphenol classes on pulmonary function parameters [76]. In a cross-sectional study in 267 Spanish COPD patients, dietary intakes of vitamin E as well as vegetables and olive oil, rich in vitamin E and polyphenols, have been shown to be inversely correlated with serum markers of oxidative stress, especially in current smokers [77].…”
Section: Individual Foods and Nutrients Lung Function And Copdmentioning
confidence: 99%
“…In a recent randomized trial in COPD patients, supplementation with flavonoids in the form of oligomeric pro-anthocyanidins extracted from grape seeds was effective in improving oxidative stress and lipid profile, but not lung function parameters after 8 weeks [75]. More recent observational findings in a Mediterranean population confirmed protective effects of the intake of various polyphenol classes on pulmonary function parameters [76]. In a cross-sectional study in 267 Spanish COPD patients, dietary intakes of vitamin E as well as vegetables and olive oil, rich in vitamin E and polyphenols, have been shown to be inversely correlated with serum markers of oxidative stress, especially in current smokers [77].…”
Section: Individual Foods and Nutrients Lung Function And Copdmentioning
confidence: 99%
“…Studies in mice model and human volunteers showed their presence in numerous tissues (83,84). They are also found to be associated with better pulmonary functions in epidemiological studies (85). These findings are encouraging to consider polyphenols as an integral part of nutritional immunity particularly innate immune response, and tea being widely consumed drink is an important and unique source of essential micronutrients and vitamins as well.…”
Section: Discussionmentioning
confidence: 64%
“…Polyphenols, which include phenolic acids, flavonoids, stilbenes, lignans and secoiridoids, seem to positively influence the human gut microbiota through inhibition of potential pathogens such as Helicobacter pylori and Staphylococ cus species and favoring the enrichment of other potential beneficial species, such as Lactobacillus and Bifidobacteria [144][145][146][147][148][149]. Polyphenols have also been associated with chronic disease, cancer and neurodegenerative disease prevention [150][151][152][153].…”
Section: Nutrition and Dietary Supplements Could Affect Microbiota Dymentioning
confidence: 99%